Public Statutes of the State of Tennessee, since the Year 1858, at 108, 1869-70 ch. 22, § 2 (Nashville, 1871). - (:unkn) unknown (My University, 1869)
That it shall not be lawful for any qualified voter or other person attending any election in this State, or for any person attending any fair, race course, or other public assembly of the people, to carry about his person, concealed or otherwise, any pistol, dirk, Bowie-knife, Arkansas toothpick, or weapon in form, shape, or size resembling a Bowie knife or Arkansas tooth-pick, or other deadly or dangerous weapon.
Keywords: CARRY; CARRY - SENSITIVE PLACES